Investigation of improvements in aircraft braking design - Bailey, David A. (Cranfield University, 2004)
This work investigates and provides a methodology that enables better prediction of brake performance. Aircraft brake performance depends on the tribological properties of the friction couple used in the brake design. The behaviour of this couple combines both surface and bulk characteristics of the material. The increase in aircraft performance requirements has led to the development of new brake designs and new friction materials. The development of brakes for large commercial aircraft has stabilised to that of a carbon-carbon composite multi-disk brake design. The results of this investigation established a relationship between mean mass loading and the mean friction radius of the brake. This relationship provides a statistically good description of the results and will provide the brake performance engineer with a useful tool. In addition, the variance within the results of the 100 Normals aircraft qualification programme was also studied. In this case the relationship is not particularly good at describing the results. A case study has been included to promote further understanding of the developed methodology and to illustrate some of the trade-offs required when designing a carbon brake. The design of a multi-disk brake is a complex engineering task that requires many specialist engineering disciplines such as structural analysis and dynamic analysis etc. The wider context of aircraft braking is even broader and requires not only mechanical engineering skills but also electronic and software engineering. This research addresses all aspects of system integration and provides a framework of understanding on the interaction and dependencies of the various components.